Calcium homeostasis behavior and cardiac function on left ventricular remodeling by pressure overload - Mazeto, I. F. S. [UNESP] (2021)
Sarcoplasmic reticulum Ca2+-ATPase (SERCA2a) and sarcolemmal Na+/Ca2+ exchanger (NCX1) structures are involved in heart cell Ca2+ homeostasis. Previous studies have shown discrepancies in their function and expression in heart failure. The goal of this study was to evaluate heart function and hypertrophied muscle Ca2+-handling protein behavior under pressure overload. Twenty male Wistar rats were divided into two groups: Aortic stenosis (AoS), induced by a clip placed at the beginning of the aorta, and Control (Sham). After 18 weeks, heart function and structure were evaluated by echocardiogram. Myocardial function was analyzed by isolated papillary muscle (IPM) at basal condition and Ca2+ protein functions were evaluated after post-pause contraction and blockage with cyclopiazonic acid in IPM. Ca2+-handling protein expression was studied by western blot (WB). Echocardiogram showed that AoS caused concentric hypertrophy with enhanced ejection fraction and diastolic dysfunction inferred by dilated left atrium and increased relative wall thickness. IPM study showed developed tension was the same in both groups. AoS showed increased stiffness revealed by enhanced resting tension, and changes in Ca2+ homeostasis shown by calcium elevation and SERCA2a blockage maneuvers. WB revealed decreased NCX1, SERCA2a, and phosphorylated phospholambam (PLB) on serine-16 in AoS. AoS had left ventricular hypertrophy and diastolic dysfunction compared to Sham; this could be related to our findings regarding calcium homeostasis behavior: deficit in NCX1, SERCA2a, and phosphorylated PLB on serine-16.